At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
- -5
Step-by-step explanation:
Given:
- f(x) = x² - 14 and g(x) = 9 - x
Find (f-g)(6):
- g(6) = 9 - 6 = 3
- (f-g)(6) = f(g(6)) = f(3) = 3² - 14 = 9 - 14 = -5
f(x)=x^2-14
g(x)=9-x
Find g(6)
[tex]\\ \sf\longmapsto g(6)=9-6=3[/tex]
Now
[tex]\\ \sf\longmapsto (f-g)(x)=f(g(x))[/tex]
[tex]\\ \sf\longmapsto f(g(6))[/tex]
[tex]\\ \sf\longmapsto f(3)[/tex]
[tex]\\ \sf\longmapsto 3^2-14[/tex]
[tex]\\ \sf\longmapsto 9-14[/tex]
[tex]\\ \sf\longmapsto -5[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.